Thomas Hobbes and the geometry of the Commonwealth: notes on the state of nature from the history of science - Orozco-Echeverri, Sergio H. (Estudios de Filosofía, 2009)
This article pretends to shed light on Hobbes’s concept of state of nature, through a reading of his conception of knowledge which makes possible to relate him with the ‘New Science’ or the Scientific Revolution. In consequence, this article relates Hobbes with some problems and traditions of the Scientific Revolution through a fresh reading of his theory of knowledge, whence the concept of state of nature is rede ned in terms of integral cause; this makes possible to argue the need of Commonwealth, excluding the anthropological pessimism traditionally attributed to Hobbes.